Batasan Tanggungjawab Notaris Terhadap Akta Autentik Yang Dibuatnya - Erlan Ardiansyah; Mohammad Saleh; Rahmia Rachman (Magister Kenotariatan, Universitas Jambi, 2022)
This research examine the legal consequences of a sale and purchase deed canceled by the court on buyers who have good faith. This research purpose to analyze and criticize the PPAT responsibilitie of the land deed whose deed was canceled by the court as well as legal protection for buyers with good intentions as a result of the sale and purchase. This research uses a normative juridical research method, which is carried out by examining legal materials, such as research on positive law. This research uses three legal approaches, namely the legal approach, the conceptual approach and the case approach. The legal materials used in this research are primary legal materials, secondary legal materials and tertiary materials. Analysis of legal materials is carried out by interpreting all laws and regulations. This research concludes that PPAT can be held accountable individually and legally. Legal responsibilities are in the form of civil and administrative responsibilities. PPAT civil liability can be held accountable for returning the status of ownership rights in administrative responsibility in accordance with the PPAT Code of Ethics may be imposed in the form of reprimands, warnings, temporary dismissals from members as contained in article 7 paragraph (1) of the Profession Code of Ethics PPAT Abstrak Kewenangan Notaris dalam membuat akta autentik sebanding dengan tanggungjawabnya, karena pertanggungjawaban tersebut terus melekat kepada notaris meskipun notaris tersebut sudah pensiun. Namun, adakalanya notaris khilaf dan membuat kesalahan dalam membuat akta autentik baik yang disengaja maupun yang tidak disengaja. Apabila hal tersebut terjadi dan dikemudian hari ternyata karena perbuatan notaris tersebut menimbulkan kerugian kepada para pihak, apakah notaris wajib mempertanggungjawabkan hal tersebut? Sejauh mana batasan tanggung jawab notaris?. Penelitian ini menggunakan metode Yuridis Empiris. Hasil dari penelitian ini apabila Notaris membuat kesalahan dalam membuat akta autentik sehingga merugikan orang lain, sepanjang pihak yang dirugikan dapat membuktikan kesalahan itu akibat kelalaian maupun kesengajaan Notaris, maka Notaris dapat dimintakan pertanggungjawaban dari sudut pandang keperdataan yakni dengan membayar ganti rugi, selanjutnya pertanggung jawaban administrasi apabila Notaris tersebut terbukti melakukan maka dapat dikenakan sanksi berupa peringatan tertulis, pemberhentian sementara, pemberhentian dengan hormat dan pemberhentian dengan tidak hormat, sedangkan dari sudut pandang hukum pidana apabila Notaris terbukti sengaja atau disadari membuat atau bekerja sama dan menandatangani suatu akta palsu maka dikenakan pidana penyertaan pemalsuan akta.